The internationalization of Brazilian higher education in the Dilma Rousseff government (2011-2014): The case of the Science without Borders program - Bischoff, Viviane; Machado, Marcelo André (Education Policy Analysis Archives, 2022)
The Science without Borders (SwB) program, created during the first term of ex-President Dilma Rousseff (2011-2014), was the most ambitious official program for the internationalization of Brazilian higher education. Despite the large mobilization of actors and resources involved, its impacts were not clearly perceived, as well as the lessons learned for public management and the program gaps were not sufficiently criticized. Thus, due to the abrupt way that the SwB was interrupted in later governments, this article sought to critically analyze the motivators, the actors involved and the results of the program. Therefore, in addition to bibliographic and documentary research, in-depth interviews were conducted with three actors directly involved in the creation and execution of the SwB, at the time. Although some positive results of the SwB have been identified, especially with regard to the number of students contemplated, the analysis of the data points to important gaps such as the personal centralization of the program, the lack of reciprocity on the part of the countries that received investments from the SwB and the program's misalignment with the Brazilian foreign policy of the period.